Observance of the Law and Charismatic Activity in Matthew - Schweizer, Eduard (New Testament studies, 1970)
The topic of my paper is particularly suitable for a Presidential Address to our Society, because so many of you have contributed, in no inconsiderable way, to the elucidation of its problems. What I shall try to do is simply to bring together some of the results of your work and then to build upon them. We have, in our common research, reached a point where it makes sense to look back on what we have discovered and to put up some signposts to mark our future course. When I say so, it is not merely an act of politeness; it is rather the expression of my appreciation of so many contributions from you without which my understanding of the first Gospel would not have been possible.